Assay optimization for measuring the alternate complement pathway activity in Asian seabass (Lates calcarifer) - Sri Dwi Hastuti; MARY D. BARTON; STEPHEN B. PYECROFT; MAURIZIO COSTABILE (Society for Indonesian Biodiversity, 2020)
Abstract. Hastuti SD, Barton MD, Pyecroft SB, Costabile M. 2020. Assay optimization for measuring the alternate complement pathway activity in Asian seabass (Lates calcarifer). Biodiversitas 21: 3034-3040. Complement proteins are one component of innate immunity present in fish. The measurement of complement activity in fish can be used to monitor the health status of fish. This is particularly important in Asian seabass (Lates calcarifer) aquaculture, where disease can impact on productivity. We have found an optimal condition assay for measuring the alternate complement pathway (ACP) activity of Asian seabass which includes Magnesium chloride (MgCl2) concentration, buffer pH, incubation temperature and incubation time. The assay was optimized using pooled serum of Asian seabass, diluted in Magnesium ethylenediamine tetraacetic acid gelatine veronal buffer (Mg-EDTA-GVB) and added with Rabbit red blood cells (RRBC) suspension. Subsequently, the suspension was incubated and centrifuged. The supernatant was removed and transferred to a well plate and the optical density (OD) was measured at 540 nm. The optimal condition obtained included a 7.5 mM MgCl2, pH optimum of 7.5, 25°C incubation temperature, and a 30 minutes incubation period. The presently developed assay was robust, rapid, and reliable to be used in monitoring the health status of Asian seabass in aquaculture farms. It can be used as guidance in further immunological studies on this fish.